Pengaruh Keragaman Menu, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Warung Ketan Ibu’e Amik Desa Tulungrejo Kecamatan Pare Kabupaten Kediri - Achmad Nur Cahyo; M. Hufron; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to examine the effect of menu diversity, price, and brand image on purchasing decisions at Warung Ketan Ibu'e Amik, Tulungrejo Village, Pare District, Kediri Regency. The population in the study were 900 consumers, and the sample of this study used a purposive sampling technique totaling 90 consumers of Warung Ketan Ibu'e Amik. The data analysis method used in this research is instrument test, normality test, classical assumption test, multiple linear analysis, and hypothesis testing.The results of this study found a conclusion, namely that partially menu diversity has a positive effect on purchasing decisions, price has a positive effect on purchasing decisions, brand image has no effect on purchasing decisions, while simultaneously menu diversity, prices, and brand image have a positive effect on purchasing decisions. .Keywords: Menu Diversity, Price, Brand Image, Purchase Decision